2003
DOI: 10.1038/sj.onc.1206518
|View full text |Cite
|
Sign up to set email alerts
|

High levels of luteinizing hormone analog stimulate gonadal and adrenal tumorigenesis in mice transgenic for the mouse inhibin-α-subunit promoter/Simian virus 40 T-antigen fusion gene

Abstract: Transgenic (TG) mice expressing the Simian virus 40 T-antigen under the control of the murine inhibin-a promoter (Inha/Tag) develop granulosa and Leydig cell tumors at the age of 5-6 months, with 100% penetrance. When these mice are gonadectomized, they develop adrenocortical tumors. Suppression of gonadotropin secretion inhibits the tumorigenesis in the gonads of intact animals and in the adrenals after gonadectomy. To study further the role of luteinizing hormone (LH) in gonadal and adrenal tumorigenesis, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 48 publications
(57 reference statements)
2
28
0
1
Order By: Relevance
“…It has been shown that the castrated male mice developed adrenocortical tumors more slowly than gonadectomized females along with the ectopic LHR expression (Bielinska et al 2003). Moreover, the elevated LH levels induced abundant ectopic LHR expression and acted as a tumor promoter selectively only in the intact female doublepositive TG mice, where bLHb-CTP mice producing constitutively elevated levels of LH (Risma et al 1995) were crossbred with inha/Tag TG mice (Mikola et al 2003). This never happened in the male double-positive mice (Mikola et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the castrated male mice developed adrenocortical tumors more slowly than gonadectomized females along with the ectopic LHR expression (Bielinska et al 2003). Moreover, the elevated LH levels induced abundant ectopic LHR expression and acted as a tumor promoter selectively only in the intact female doublepositive TG mice, where bLHb-CTP mice producing constitutively elevated levels of LH (Risma et al 1995) were crossbred with inha/Tag TG mice (Mikola et al 2003). This never happened in the male double-positive mice (Mikola et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The adrenal tumors and a tumor-derived cell line (Ca1) express very high levels of LHR (Kananen et al 1996a, and the growth and steroidogenesis of the adrenal tumors were shown to be dependent on LH stimulation (Mikola et al 2003). The post-castration elevation of LH levels apparently induced the ectopic LHR expression, which together with the potent oncogene Tag expression triggered adrenocortical tumorigenesis (Mikola et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been different reports in different tissues and models showing different mechanisms of the SV40 Tag oncogene -induced cancer development. Examples include mouse pancreatic islet carcinoma (14); neoplastic transformation of murine fibroblasts through signal transducer and activator of transcription-3 (14), p130-E2F/p107-E2F (13), and VEGF (17) gene up-regulation as SV40 Tag targeting factors in gonadal and adrenal tumorigenesis (16); and mesothelial tumor by affecting telomerase activity (44).…”
Section: Discussionmentioning
confidence: 99%
“…There seems to be ample evidence that other factors contributing to the transformation potential of SV40 Tag are yet to be fully elucidated. The ability of T antigen to deregulate cell proliferation depends on its specific interaction with a variety of host cell proteins, studies of which have led to the elucidation of many different signaling pathways in different cancer modeling systems (12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%